Pemberdayaan Perempuan Melalui Kelompok Wanita Tani dalam Meningkatkan Kesejahteraan Keluarga - Cyntria Nursalamah; Dadang Kuswana; Indira Sabet Rahmawaty (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2020)
This paper aims to find out the process, results and inhibiting and supporting factors in women's empowerment through women farmer groups in improving family welfare in Cipanjalu Village, Cilengkrang District, Kab. Bandung. The method in this study uses descriptive study method, so data collection is not guided by theory but guided by facts found during research in the field. The results of the research showed that in the planning process the community farmer group women were not involved in the process, but the government in its planning aimed at increasing self-reliance and prosperity, where empowerment was able to improve family welfare by fulfilling material, spiritual and social physical needs by involving community participation and also existing resources.